Endogenous Growth Substances And Sugar Levels in Wheat Grains During Germination - AHMED, HUSAIN S.; SAWHNEY, JAGDEV S. (The Libyan Journal of Agriculture, 2023)
Wheat (Triticum aestivum L.) grains of the cultivar ‘Sidi Misri 1' were germinated in pelri dishes at 25°C for seven days. Samples were taken daily to evaluate the level of reducing and non-reducing sugars and the type of growth substances present in the seeds during germination. After 24 hours of germination, a predominant presence of growth promoting substances were found in the extract of seeds. A growth inhibiting activity, possibly due to salicylic acid and/or coumarin, was seen on the third, fourth and fifth day of germination. No promotive or inhibitory activity was detected on the seventh day of germination. Reducing sugars were steadily increased, however, the daily increment was significant only until the fourth day of germination. The non-reducing sugars increased on the second day of germination but disappeared afterwards.